Pharmaceutical care for deaf people: a literature review (Research, Society and Development, 2023)
Pharmaceutical care is a set of measures promoted by a pharmacist in collaboration with other health professionals, as a responsible provider of drug treatment, achieving concrete results that improve the quality of life of patients. The study aims to present pharmaceutical care to deaf people, and how it develops communication between them. This is a bibliographic review, where publications indexed in three databases, LILACS, Scielo and Pubmed in Portuguese, were analyzed from 2016 to 2022. The result of the review identified that pharmacists are not prepared to make this type of care and deaf people are at a disadvantage compared to the purchase of a drug and guidance. The language barrier is a challenge that must be overcome in so that deaf people receive the necessary information about the use of medicines and health education. It can be seen that there are important studies on the offer and promotion of medical care for the deaf, developed according to different scenarios. It was concluded that the perception of deaf people and pharmacists brings libra's lack of communication as the greatest obstacle to comprehensive and humanized health care.